WORK OF THE JOINT COMMITTEE ON INCOME TAX STATISTICS. - Dohr, James L. (The Accounting Review, 1933)
Abstract Economists, statisticians, accountants and others have long realized that the various income tax returns filed with the Bureau of Internal Revenue contain a vast quantity of valuable statistical data. The American Association of University Instructors in Accounting, the American Economic Association and the American Statistical Association, designated a Joint Committee to consider the entire problem and to draft suggestions to the Bureau of Internal Revenue for the amplification, revision or elimination of the existing tabulations. This report recommends that the specific recommendations of the Committee as set forth in the report be approved in principle; that a new Joint Committee be appointed to continue the work and that a modest appropriation be made for its traveling expenses. The purpose of this article is to summarize briefly the various problems involved and the Committee's attempts at solution. Certain phases of the problem at least are of considerable importance to accountants and teachers of accounting and it is suggested that a consideration of the statistics as now published would be of interest to all of the members of the Association.